BIRD SPECIES DIVERSITY ACROSS A GRADIENT OF LAND USE IN SOUTHERN GONAREZHOU NATIONAL PARK AND ADJACENT AREAS, ZIMBABWE - C. M. Mzendah; C. Mashapa; C. H. D. Magadza; E. Gandiwa; S. Kativu (Journal of Animal and Plant Sciences, 2015)
Bird species composition and abundance across a land disturbance gradient in southern Gonarezhou National Park and adjacent areas, Zimbabwe was assessed in April 2013. Three study strata based on land use category were delineated, namely protected Manyanda Pan inside Gonarezhou National Park, unprotected Manjinji Pan and cultivated lands around Manjinji Pan. Bird census points were randomly pegged across the three study strata where bird species and numbers were recorded. Habitat condition of the study strata was estimated using the Global Monitoring Framework method. The study recorded a total of 2706 birds belonging to 131 species and 60 families from the three sites. With its dense woodlands, Manjinji Pan recorded significantly higher bird species diversity (H′ = 4) than either the degraded Manyanda Pan (H′ = 2.3) or the cultivated lands (H′ = 2.6). Bird species evenness was highest in Manjinji Pan (J′ = 0.59), whereas, lowest species evenness (J′ = 0.18) was recorded on cultivated lands.  The results suggest that land use type and woodland status likely influence bird species diversity in the study area. The study recommended for conservation of the remaining forest and wetland fragments in southern Zimbabwe even in unprotected areas in order to maintain avifaunal diversity.
Keywords: bird species diversity; land use; vegetation cover; habitat disturbance